2018
DOI: 10.1186/s12881-018-0647-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice site mutation in WAS gene in patient with Wiskott-Aldrich syndrome and chronic colitis: a case report

Abstract: BackgroundWiskott-Aldrich syndrome is an X-linked recessive immunodeficiency due to mutations in Wiskott-Aldrich syndrome (WAS) gene. WAS gene is encoded for a multifunctional protein with key roles in actin polymerization, signaling pathways, and cytoskeletal rearrangement. Therefore, the impaired protein or its absence cause phenotypic spectrum of the disease. Since identification of novel mutations in WAS gene can help uncover the exact pathogenesis of Wiskott-Aldrich syndrome, the purpose of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It could be due to the loss of functional mutations in the WAS gene located in the X chromosome (position Xp11.22-p11.23), and the pathogenic mutations that occur within the exons and introns [ 54 , 55 ]. As previously reported, at least 49 mutations (either nonsense, missense, frameshift, splice site or complex) occurred in the WAS gene [ 15 , 50 , 51 , 52 , 56 , 57 , 58 , 59 ].…”
Section: Immune Thrombocytopenia and Autoimmune Diseasesmentioning
confidence: 89%
“…It could be due to the loss of functional mutations in the WAS gene located in the X chromosome (position Xp11.22-p11.23), and the pathogenic mutations that occur within the exons and introns [ 54 , 55 ]. As previously reported, at least 49 mutations (either nonsense, missense, frameshift, splice site or complex) occurred in the WAS gene [ 15 , 50 , 51 , 52 , 56 , 57 , 58 , 59 ].…”
Section: Immune Thrombocytopenia and Autoimmune Diseasesmentioning
confidence: 89%
“…In conclusion, Wiskott-Aldrich syndrome is a rare X-linked disorder that predominantly affects males. Male patients with congenital thrombocytopenia and small platelets must have their WAS gene mutation and WASP expression evaluated as soon as possible using molecular genetic techniques and protein detection [ 22 ]. In this study, we identified a novel pathogenic WAS gene mutation (c.931 + 5G > C (splicing)) causing XLT with mild clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotype can be explained by exon skipping or intron retention (Inoue et al, 2004). Splicing sites affected by mutations have been described for many pathological phenotypes: neurofibromatosis type 1 (Jang et al, 2016), familial hypercholesterolemia (Shakhtshneider et al, 2017), Wiskott-Aldrich syndrome and chronic colitis (Esmaeilzadeh et al, 2018), hypophosphatemic rickets (Ma et al, 2015), and others. Mutations affecting splicing have been found not only in canonical splicing sites but also in introns and exons and may have a tissue-specific effect, as in familial dysautonomia (Slaugenhaupt et al, 2001;Abramowicz, Gos, 2018).…”
Section: Discussionmentioning
confidence: 99%